Imbalance of Angiogenesis in Diabetic Complications: The Mechanisms - Tahergorabi, Zoya (Medknow Publications & Media Pvt Ltd, 2012)
Type 2 diabetes mellitus is a complex disease and a chronic health-care problem. Nowadays, because of alteration of lifestyle such as lack of exercise, intake of high fat diet subsequently obesity and aging population, the prevalence of diabetes mellitus is increasing quickly in around the world. The international diabetes federation estimated in 2008, that 246 million adults in worldwide suffered from diabetes mellitus and the prevalence of disease is expected to reach to 380 million by 2025. Although, mainly in management of diabetes focused on hyperglycemia, however, it is documented that abnormalities of angiogenesis may contribute in the pathogenesis of diabetes complications. Angiogenesis is the generation of new blood vessels from pre-existing ones. Normal angiogenesis depends on the intricate balance between angiogenic factors (such as VEGF, FGF(2), TGF-β, angiopoietins) and angiostatic factors (angiostatin, endostatin, thrombospondins). Vascular abnormalities in different tissues including retina and kidney can play a role in pathogenesis of micro-vascular complications of diabetes; also vascular impairment contributes in macrovascular complications e.g., diabetic neuropathy and impaired formation of coronary collaterals. Therefore, identifying of different mechanisms of the diabetic complications can give us an opportunity to prevent and/or treat the following complications and improves quality of life for patients and society. In this review, we studied the mechanisms of angiogenesis in micro-vascular and macro-vascular complications of diabetes mellitus.